Isolation and Identification of Anthralin From the Roots of Rhubarb Plant (Rheum palmatum) - A. Ashnagar; N. Gharib Naseri; H. Haidari Nasab (E-Journal of Chemistry)
Anthralin is medically and chemically an important compound which can be found in rhubarb roots. Anthralin and anthralin derivatives have been used as antipsoriatic drugs. In this research, pure anthralin was isolated from the rhubarb roots by maceration and Soxhlet extraction methods in various polar and non-polar solvents. Successive TLC and column chromatography on silica gel with chloroform as the mobile phase afforded two distinct fractions with Rf= 0.54 and 0.61. The 1HNMR, 13CNMR, IR, UV and MS spectra showed that the fraction with Rf= 0.61 was anthralin. In both methods, methanol was found to be the most suitable solvent for extraction.